2017
DOI: 10.1038/s41598-017-04268-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Crucial Immunogenic Epitopes in Major Peanut Allergy Protein, Ara h2, via Novel Nanoallergen Platform

Abstract: Current methods for detection and diagnosis of allergies do not provide epitope specific immunogenic information and hence lack critical information that could aid in the prediction of clinical responses. To address this issue, we developed a nanoparticle based platform, called nanoallergens that enable multivalent display of potential allergy epitopes for determining the immunogenicity of each IgE binding epitope. By synthesizing nanoallergens that present various epitopes from the major peanut allergen, Ara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…Our results show that specific peptide reactivity is highly variable between individual patients. A similar observation was reported by Deak et al 47 They developed "nanoallergens", a nanoparticle-based platform for multivalent testing of potential epitopes of Ara h 2 in a cell-based assay. They concluded that some epitopes are more "im-…”
Section: Patient-specific Allergen Recognition Patternssupporting
confidence: 73%
“…Our results show that specific peptide reactivity is highly variable between individual patients. A similar observation was reported by Deak et al 47 They developed "nanoallergens", a nanoparticle-based platform for multivalent testing of potential epitopes of Ara h 2 in a cell-based assay. They concluded that some epitopes are more "im-…”
Section: Patient-specific Allergen Recognition Patternssupporting
confidence: 73%
“…Based on their medical history, symptoms of the IgE-mediated peanut allergy involved skin, respiratory tract, gastrointestinal tract, and cardiovascular system. Twelve sera from US peanut-allergic patients with a strong history of peanut-induced immediate hypersensitivity and peanut-specific IgE ≥13 KAU/L (ImmunoCap; Thermo Fischer Scientific) in serum were also included (Table S1, sera [21][22][23][24][25][26][27][28][29][30][31][32]. All adult patients and the parents or guardians of minors signed informed consent.…”
Section: Human Seramentioning
confidence: 99%
“…This absence of distinction is illustrated inFigure 4with nAra h 2 and rAra h 2 displaying similar IgE-binding capacities although the absence of hydroxyproline in rAra h 2 has been shown to reduce the binding affinity of IgE recognizing the DPYSP OH S motifs in nAra h 2. In contrast, assays such as IgE-binding competitive inhibition or in vitro mast cell degranulation can evidence differences of binding affinity and could thus demonstrate the higher allergenic activity of nAra h 2 compared with rAra h 2 22,32. We therefore investigated cross-reactivity between 2S-albumins with a competitive fluidphase assay (Figure 5A).…”
mentioning
confidence: 99%
“…2 and Ara h 6 using the nanoallergen assay system developed in our laboratory (12). Nanoallergens provide multivalent display for allergen epitopes on liposomal surfaces, which are then used to evaluate their immunogenicity via in vitro mast cell degranulation responses ( Fig.…”
Section: Identification Of Immunodominant Ara H 2 and Ara H 6 Epitopementioning
confidence: 99%
“…S2). These nanoallergens multivalently present epitopes on their surfaces with high-precision and controlled stoichiometry (12,14). Nanoallergens were used to trigger degranulation response in RBL-SX38 cells [model mast cell line which expresses human IgE receptor (FceRI)] (15) primed with a specific patient serum (Fig.…”
Section: Identification Of Immunodominant Ara H 2 and Ara H 6 Epitopementioning
confidence: 99%